ANALISIS STORE ATMOSPHERE DAN LOKASI DALAM MENINGKATKAN MINAT BELI KONSUMEN PADA CV LAVIEYOLIE BERJAYA - Trijumansyah, Andry; Loda, Maria Yasinta; Solihat, Ani; Rahmayani, Rani; Iskandar, Iis (Sekolah Tinggi Ilmu Ekonomi AMM Mataram, 2019)
The increasingly high level of competition results in consumers having a high bargaining position on store atmosphere, location and buying interest of consumers. This study aims to analyze the effect of store atmosphere and location both partially and simultaneously on consumer buying interest in CV LavieYolie Berjaya. The method used in this study is a descriptive verification method. Data sources are obtained through interviews, observations, questionnaires, and literature studies. The sampling method is simple random sampling and determining the number of samples is calculated using the Slovin formula. Data collection techniques using questionnaires after testing the validity and reliability. Data analysis techniques were carried out using classical assumption tests. The results show that Store atmosphere has a positive and significant effect on consumer buying interest, location has a positive and significant effect on consumer buying interest, and Store atmosphere and location simultaneously have a positive and significant effect on consumer buying interest.